Perbandingan kinerja keuangan perusahaan sebelum dan sesudah akuisisi pada perusahaan yang terdaftar di BEI - Ningsih, Tantri Utami; Hasmarini, Maulidyah Indira (Nur Science Institute, 2025)
This study examines the differences in companies’ financial performance before and after acquisition. The sample used consists of companies listed on the Indonesia Stock Exchange that underwent acquisitions between 2020 and 2024, with a total sample size of five companies. Financial performance was assessed based on the two years before and after the acquisition. The sampling technique used was purposive sampling. Data collection techniques were conducted through financial reports from the Indonesia Stock Exchange. The variables studied included liquidity ratio (current ratio), solvency (debt-equity ratio), profitability (return on assets), market (earnings per share), and activity (total asset turnover). Data analysis methods used paired sample t-tests for normally distributed data, while non-normal data used Wilcoxon Ranks. The analysis results indicate no significant differences in the five ratios studied, namely liquidity ratio, solvency ratio, profitability ratio, market ratio, and activity ratio, before and after the acquisition.